"BLACK HAMLET": A PSYCHOANALYST DESTRANGERS A STRANGER - Bloom, Len (PINS-Psychology in Society, 2026)
First published in 1937, Wulf Sachs' Black Hamlet remains topical and controversial. It is an unconventional case-history of nearly 300 pages and a social document. A European psychoanalyst and an uneducated African healer-diviner met and strived to understand one another emotionally and socially. To a remarkable extent they succeeded. In Black Hamlet Sachs probed how individuals came to experience one another as individuals despite personal, social and cultural obstacles. Sachs was both a psychoanalyst and a socialist activist and he asked such questions as: How do individuals come to trust one another? How do they reach one another emotionally despite their personal narcissisms and those of their cultures? Black Hamlet is a book of frankly expressed impressions that suggests that strangers may be less strange than one expected, feared or was led by one's society to believe. The strangeness or otherness of other individuals is not beyond our personal or professional awareness. Winnicott in his Playing and reality has shown how "cultural experience has not found its true place in the theory used by analysts in their work and in their thinking• (Winnicott, 2002:xi). Consequently the complex relationships between psychic reality (the internal or personal) and the socio-cultural setting has been neglected Sachs did not neglect these relationships. He boldly applied Freudian insights to a specific socio cultural setting at a particular historical time. For Sachs, as for Winnicott, the intricate stresses of breaking out of personal and socio-cultural narcissisms to appreciate the individuality of "others• were a central problem for psychoanalysts.